Analisis Self Efficacy Pegawai berdasarkan Iklim Psikologis, Keterlibatan Kerja dan Kepemimpinan (Studi Kasus Pegawai Sekretariat DPRK Kabupaten Bireuen) - Rosdiana, Efi; Chadafi, M. F.; Yanna, Sri (Aceh Cooperative Care, 2025)
This study, conducted on employees of the Bireuen Regency DPRK Secretariat, aimed to empirically determine the direct and indirect impacts of psychological climate, work engagement, and leadership on self efficacy. The associative approach was applied with a quantitative approach. The data analysis used path analysis to answer the hypotheses. The sample size was 43 employees. The results showed: (1) self efficacy, based on the direct and indirect impacts of psychological climate factors, was 37.93%, work engagement factors were 55.39%, and leadership factors were 45.86%. (2) Psychological climate, work engagement, and leadership simultaneously impacted and contributed to self efficacy by 69.3%. (3) There was a causal relationship between the independent variables, with a moderate categorization.